A Cross-Sectional Trait Versus State Biomarker Analysis of Inflammatory Cytokines and miRNAs in Patients with Major Depressive Disorder - Christopher Rockson; Chandrashekaran Girish; Harivenkatesh Natarajan; Vikas Menon (Indian Journal of Psychological Medicine)
Background: Inflammatory cytokines are associated with the pathophysiology of major depressive disorder (MDD). Nevertheless, whether they are trait or state biomarkers remains unclear. We aimed to assess and compare selected cytokines, miRNAs, and oxidative stress biomarker levels between patients with MDD, first-degree relatives (FDRs), and unrelated healthy controls (UHCs). Methods: Using a cross-sectional design, we recruited patients with MDD, their FDRs and age, gender, body mass index-matched UHCs. Serum levels of IL-6, IL-1β, TNF-α, hs-CRP, and IL-10 were evaluated using the Enzyme-Linked Immunosorbent Assay (ELISA) method. We quantified the gene expressions of plasma miR-16, miR-132, and miR-1202 using Quantitative Real Time-Polymerase Chain Reaction (qRT-PCR). We estimated the total oxidant status and total antioxidant status levels in the serum by ELISA. We used sequential multiple linear regression analysis to find the association between MDD vs. UHCs (model 1), FDRs vs. UHCs (model 2), and MDD vs. FDRs (model 3) after adjusting for age, gender, and BMI as covariates. Results: The study involved 50 patients with MDD (mean age = 34.7 ± 10.1 years), 31 FDRs (mean age = 32.7 ± 12.2 years), and 50 UHCs (mean age = 34.1 ± 10.3 years). Patients with MDD had higher levels IL-6 (β = 6.04; 95% CI; 1.60 to 10.49; p = 0.008) and downregulated miR-1202 (β = –0.38; 95% CI: –0.70 to –0.06; p = 0.02) compared to FDRs with statistically significant differences. Conclusion: The higher levels of serum IL-6 and downregulated plasma miR-1202 expression in patients with MDD compared to FDRs may be a state biomarkers in MDD. However, an adequately powered study can answer these questions with certainty.